(untitled) (Bangladesh Journal of Anatomy, 2015)
Context : Two organs that can provide a good insight into pregnancy induced hypertension with and without diabetes mellitus are the placenta and the umbilical cord along with their vessels. In the present study the umbilical cord is taken from the placenta of hypertensive and diabetic mothers to measure its diameter, to observe contained vessels and its mode of attachment to the placenta. Materials and Methods: An observational and analytical type of study was conducted in the department of Anatomy, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka between November 2003 to May 2004 on umbilical cords. To study the umbilical cord, placentas were collected from fifty eight Bangladeshi women who gave birth to a single live baby through Caesarian section after 35 to 40 weeks of gestasion. Twenty of the mothers were non hypertensive, non diabetic control, twenty had pregnancy induced hypertension(PIH) and eighteen had pregnancy induced hypertension and gestesional diabetes mellitus(PIH+GDM). Results: No significant difference was found between any groups for diameter of the umbilical cord. All the umbilical cords had same number of vessels. There was variation among the mode of insertion of umbilical cord. Conclusion: Diameter of umbilical cords did not show significant difference in either of the two diseased groups with the control group in the Post Hoc option of analysis of variance (ANOVA) at 5% level. DOI: http://dx.doi.org/10.3329/bja.v12i1.22609 Bangladesh Journal of Anatomy, January 2014, Vol. 12 No. 1 pp 03-06